Molecular phylogeny of Triatomini (Hemiptera: Reduviidae: Triatominae) - Justi, Silvia Andrade (BioMed Central, 2014)
BACKGROUND: The Triatomini and Rhodniini (Hemiptera: Reduviidae) tribes include the most diverse Chagas disease vectors; however, the phylogenetic relationships within the tribes remain obscure. This study provides the most comprehensive phylogeny of Triatomini reported to date. METHODS: The relationships between all of the Triatomini genera and representatives of the three Rhodniini species groups were examined in a novel molecular phylogenetic analysis based on the following six molecular markers: the mitochondrial 16S; Cytochrome Oxidase I and II (COI and COII) and Cytochrome B (Cyt B); and the nuclear 18S and 28S. RESULTS: Our results show that the Rhodnius prolixus and R. pictipes groups are more closely related to each other than to the R. pallescens group. For Triatomini, we demonstrate that the large complexes within the paraphyletic Triatoma genus are closely associated with their geographical distribution. Additionally, we observe that the divergence within the spinolai and flavida complex clades are higher than in the other Triatoma complexes. CONCLUSIONS: We propose that the spinolai and flavida complexes should be ranked under the genera Mepraia and Nesotriatoma. Finally, we conclude that a thorough morphological investigation of the paraphyletic genera Triatoma and Panstrongylus is required to accurately assign queries to natural genera.